Genomic surveillance of extended-spectrum cephalosporin-resistant Escherichia coli isolated from poultry in the UK from 2016 to 2020 - Duggett, Nicholas; AbuOun, Manal; Stubberfield, Emma; Turner, Olivia; Randall, Luke; Horton, Robert; Nunez-Garcia, Javier; Gates, Daisy; Chanter, Jeremy; Teale, Chris; Anjum, Muna F. (Frontiers in Microbiology, 2024)
Introduction Surveillance is vital for monitoring the increasing risk of antimicrobial resistance (AMR) in bacteria leading to failures in humans and animals to treat infections. In a One Health context, AMR bacteria from livestock and food can transfer through the food chain to humans, and vice versa, which can be characterized in detail through genomics. We investigated the critical aspects of AMR and the dynamics of AMR in poultry in the UK. Methods In this study, we performed whole genome sequencing for genomic characterization of 761 extended-spectrum cephalosporinases (ESCs) harboring Escherichia coli isolated from poultry caeca and meat through EU harmonized monitoring of AMR in zoonotic and commensal bacteria from 2016 and 2018 and UK national monitoring in 2020. Results The most common ESC in 2016 and 2018 was blaCTX-M-1; however, 2020 had a greater diversity of ESCs with blaCTX-M-55 dominant in chickens and blaCTX-M-15 more prevalent in turkeys. Co-resistance to sulphonamides, tetracycline, and trimethoprim was widespread, and there were several positive correlations between the sequence types (STs) and ESC genes. We identified certain AMR genotypes and STs that were frequent each year but not as successful in subsequent years, e.g., ST350 harboring blaCTX-M-1, sul2, and tetA-v4.Phylogenetic comparison of isolates prevalent in our panel with global ones from the same STs available in public databases showed that isolates from the UK generally clustered together, suggesting greater within-country than between-country transmission. Discussion We conclude that future genomic surveillance of indicator organisms will be invaluable as it will enable detailed comparisons of AMR between and within neighboring countries, potentially identifying the most successful sequence types, plasmids, or emerging threats.